ENTREPRENEURSHIP DEVELOPMENT MODEL for MIGRANT WORKERS (Case Study of Migrant Workers in Hongkong) - Jawoto Nusantoro; Ery Baskoro (Akuisisi: Jurnal Akuntansi, 2015)
ABSTRACT Migrant workers have became a phenomenon for the government. They have been considered as foreign exchange heroes for the government but on the contrary there is something untouchable thing after they have done their contracts. Do they will decide to continue their contracts or cut off their contracts and go back to Indonesia with all the problems embedded to them. Entreprenuership is one of the solution for them as their provision skill after they go back to Indonesia and not working as migrant workers anymore. Based on the problem, an alternative model must be found for  the problem solver. The Objectives of this research is to make an entrepreneurship development model for the migrant workers. The specifif objectives for the research is to implement the entrepreneurship development model for the migrant worker that can be used by migrant workers. The Research method used for the research is multiple case study. The collecting data method used for the research is combinating approach (triangulation). There are survey, observation, field study PRA (Participatory rural appraisal) and action research. Research level used for the research is explorative and analysis method used for the research is qualtitative. Key words : Entrepreneurship, migrant